Reflectance spectroscopy: a non-invasive strategy to explore skin reactions to topical products - Mancuso, Antonia; d’Avanzo, Nicola; Cristiano, Maria Chiara; Paolino, Donatella (Frontiers in Chemistry, 2024)
Reflectance spectroscopy has emerged as a powerful analytical technique in the field of dermatology, offering a non-invasive strategy to assess several cutaneous properties and skin response to topical products. By analyzing reflected light across different wavelengths, reflectance spectroscopy allows the quantification of cutaneous parameters, such as erythema index and melanin content. Moreover, this analytical technique enables the monitoring of any changes in skin physiology facilitating the assessment of long-term effects of topical products as well as predicting cutaneous diseases. This review provides an overview of the application of reflectance spectroscopy in investigating skin properties and reaction to topical applied products, including both pharmaceutical and cosmetic formulations, thereby aiding in the development of personalized solutions tailored to individual needs.